PENGGUNAAN ALAT BUKTI SEBAGAI DASAR PENETAPAN TERSANGKA PADA PENYIDIKAN TINDAK PIDANA KECELAKAAN KAPAL WISATA YANG MENGAKIBATKAN MATINYA ORANG - Dekri, Yuli (UNES Law Review, 2022)
The skipper is given responsibility by Law Number 17 of 2008 concerning Shipping related to ship safety and security. The evidence that is the basis for determining the suspect in the tourist ship accident case that resulted in the death of a person in the case file number Bp/44/XII/2019/Reskrim/Parisan Police is witness statements and other evidence. Based on the theory of evidence, to prove someone's negligence is to see whether someone has used the precautionary principle or not, see how people generally take action when in conditions like those experienced by the perpetrator and whether someone has taken the action that should have been done or not. The suspect in this case is the captain of the ship because he was proven to have sailed from the coast of Gandoriah Pariaman to Angso Duo Pariaman Island and without having a Sailing Approval Letter issued by the Syahbandar. Other evidence is witness testimony stating that the ship exceeds the specified capacity as well as a certificate of proficiency for the captain. The obstacle in collecting evidence which is the basis for determining the suspect in the tourist ship accident case that resulted in the death of the person in the case file Number Bp/44/XII/2019/Reskrim/Parisan Police is the witness testimony given by the suspect's statement which does not match. Determining who was negligent due to negligence is not always the suspect. The number of legal substances that will be applied and all the elements contained in several articles that are applied each must be supported by a minimum of 2 (two) pieces of evidence.